The level of Β-2-microglobulin, albuminuria in patients with chronic heart failure and atrial fibrillation depending on the functional state of the kidneys. - Muhammad Muhammad (Medičnì Perspektivi)
Despite the advances in the treatment of chronic heart failure (CHF) the mortality of patients remains high. Development of renal dysfunction is one of the most common conditions comorbid with CHF. Atrial fibrillation (AF) is the most frequent arrhythmia in clinical practice, the prevalence of which is increasing. The risk factors and mechanisms of AF development and renal dysfunction largely coincide. The markers of early renal damage in patients with CHF and AF are presented and analyzed. The data suggest that the degree of tubular damages assessed by β-2-microglobulin level in blood serum and AU is not always correlate with changes of GFR, but has significant variability.